Efektivitas Perbup Bombana No. 10/2019 tentang Santunan Kematian bagi Masyarakat Miskin di Kabupaten Bombana - Harun Al Rasyid (Institut Agama Islam (IAIN) Kendari, 2025)
The Bombana Regency Government has implemented social assistance in the form of death benefits as regulated in Bombana Regent Regulation No. 10 of 2019 concerning Guidelines for the Provision of Social Assistance in the Form of Death Benefits for the Poor in Bombana Regency. In its implementation, there are still cases where poor people who have died do not receive the intended assistance. Based on this issue, a study was conducted to assess the effectiveness of Bombana Regent Regulation No. 10 of 2019 on Guidelines for the Provision of Social Assistance in the Form of Death Benefits for the Poor in Bombana Regency and to identify the supporting and hindering factors in the implementation of Bombana Regent Regulation No. 10 of 2019 on Guidelines for the Provision of Social Assistance in the Form of Death Benefits for the Poor in Bombana Regency. The typology of this research is normative-empirical legal research using a statutory approach and a case approach. The results of this study indicate that the implementation of death benefits has proven to be quite effective. Clear rules and data, as well as adequate facilities, are supporting factors in the death benefit program in Bombana Regency. Meanwhile, the hindering factors are insufficient funding and socialization by the local government. Keywords: Effectiveness, Death Benefits, Poor Communities.